La foire aux valeurs - Georges Brunel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The author examines the contemporary use of the term "value", in touch with the heritage, and returns on the theoretical and practical employment by Aloïs Riegl.